2019
DOI: 10.1089/jmf.2019.0093
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration ofHoodia parvifloraAlleviates Insulin Resistance and Nonalcoholic Steatohepatitis

Abstract: Metabolic syndrome is recognized as a proinflammatory condition leading to hepatic steatosis and nonalcoholic steatohepatitis (NASH). We tested the effects of a succulent species Hoodia parviflora N.E. Br., of the genus Hoodia sweetex Dence, on animal models of NASH and insulin resistance (ob/ob mouse and the sand rat Psammomys obesus). IL6 secretion was evaluated by ELISA and hepatic signal transducer and activator of transcription 3 by Western blot. We followed liver enzymes, weight, glucose, hepatic histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…These effects were attributed to the potential immunomodulatory effect of GSLs [19,37]. They also support a potential oralimmunotherapy-based mechanism of action recently described for several compounds [21,25,29,[37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Discussionsupporting
confidence: 81%
“…These effects were attributed to the potential immunomodulatory effect of GSLs [19,37]. They also support a potential oralimmunotherapy-based mechanism of action recently described for several compounds [21,25,29,[37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Discussionsupporting
confidence: 81%
“…22 Because of insulin resistance, the body would present lipid metabolism disorder with significantly increased lipolysis of fat tissues, thus a lot of free fatty acids would be released into the blood to promote liver intake of free fatty acids from the blood, thereby eventually inducing lipid accumulation in liver cells, especially TG accumulation, which is directly related to the development and progression of NASH. 23,24 From this study, MRTF-A knockout can reduce the blood glucose, plasma insulin and hepatic TG of NASH mice. In the similar vein, another study also reported that MRTF-A deficiency can effectively ameliorate HFD-induced obesity, inflammatory responses, insulin resistance and hepatic steatosis.…”
Section: Discussionmentioning
confidence: 71%
“…However, latestage programs have thus far shown marginal efficacy and have troubling safety signals, suggesting the need for alternative approaches. In this issue of the journal, Mizrahi et al 12 provide promising data demonstrating antiinflammatory effects of Hoodia extracts (Hesperaloe parviflora), which result in marked improvements in chemically induced immune hepatitis. They further show that H. parviflora improves glucose tolerance as well as hepatic triglycerides and liver histology in both genetic (ob/ob mice) and nutritionally induced (high-energy diets) models of NAFLD/NASH.…”
mentioning
confidence: 99%